REVIEW OF THE TRAINING MANUAL Y.L. YURINETS "CONSTITUTIONAL LAW OF UKRAINE" - Holosnichenko, Dmytro (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Approaches and views in the field of modernization of the Basic Law, which is currently underway in Ukraine, are characterized by dynamism. Therefore, the preparation by the author Y.L. Yurynets of the textbook “Constitutional Law of Ukraine” is appropriate and relevant. The textbook systematically presents the material of the course “Constitutional Law of Ukraine”. The content of the textbook reflects the content of the relevant curriculum and structurally corresponds to the Constitution of Ukraine itself, takes into account the latest amendments to the Constitution of Ukraine. In general, the reviewed textbook is an original creative work, based on an organic combination of theoretical concepts with practical experience in teaching the course, and will be useful for use in the educational process.